2009
DOI: 10.1038/ni.1706
|View full text |Cite
|
Sign up to set email alerts
|

Cross-regulation of signaling by ITAM-associated receptors

Abstract: An important function of receptors that signal through immunoreceptor tyrosine-based activation motifs (ITAMs) is to regulate signaling by heterologous receptors. This review describes mechanisms by which ITAM-associated receptors modulate signaling by Toll-like receptors (TLRs), tumor necrosis factor receptor family members and cytokine receptors that use the Jak-STAT signaling pathway, and the biological importance of this signal transduction cross-talk. ITAM-mediated crossregulation can either augment or da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
197
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(209 citation statements)
references
References 97 publications
9
197
0
3
Order By: Relevance
“…This was found not to be due to a general impairment of dense granule secretion, as platelets released prominent and almost normal amounts of ATP (3 µM) when subsequently challenged with 0.1 U/ml thrombin. Under all tested conditions platelet aggregation, as expected, was prominently precluded by abciximab ( Figure 5B FcRs or β integrins for PLC activation and, in turn, Ca 2+ and DAG signalling (for review see [19]). Using isolated platelets from a Glanzmann's thrombasthenia patient ( Figure 6) we found that convulxin (7.5 ng/ml) as well as Pam3CSK4 (7.5 and 30 µg/ml) evoked both LAT Tyr191 and PLC2 Tyr759 phosphorylation ( Figure 6A).…”
Section: Platelet Dense Granule Secretion and Aggregation In Responsementioning
confidence: 97%
See 2 more Smart Citations
“…This was found not to be due to a general impairment of dense granule secretion, as platelets released prominent and almost normal amounts of ATP (3 µM) when subsequently challenged with 0.1 U/ml thrombin. Under all tested conditions platelet aggregation, as expected, was prominently precluded by abciximab ( Figure 5B FcRs or β integrins for PLC activation and, in turn, Ca 2+ and DAG signalling (for review see [19]). Using isolated platelets from a Glanzmann's thrombasthenia patient ( Figure 6) we found that convulxin (7.5 ng/ml) as well as Pam3CSK4 (7.5 and 30 µg/ml) evoked both LAT Tyr191 and PLC2 Tyr759 phosphorylation ( Figure 6A).…”
Section: Platelet Dense Granule Secretion and Aggregation In Responsementioning
confidence: 97%
“…Unlike in some other 'classical' immune cells this cascade was not indirectly induced via  3 integrins [19,20] as demonstrated by the use of platelets from a patient with…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their extracellular regions contain either four or two immunoglobulin-like domains arranged linearly. Natural ILT2 consists of four extracellular domains and a cytoplasmic tail of four ITIMs, which mediate its cell-signaling effects (Hamerman and Lanier, 2006;Ivashkiv, 2009). Engagement of ILT2 triggers tyrosine phosphorylation of ITIMs and the subsequent recruitment of a number of protein tyrosine phosphatases (Binstadt et al, 1996), leading to downregulation of the signaling mediated by activating receptors (Colonna et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…M-CSF as well as RANKL-deficient mice show severe osteopetrosis (5,6,12). In addition to these molecules, several transcription factors, such as NF-kB, NFAT cytoplasmic 1 (NFATc1), micropthalmia transcription factor (MITF), PU.1, and c-Fos, are vital for osteoclast formation (13)(14)(15). PU.1 is essential for development of myeloid cells.…”
mentioning
confidence: 99%